Analisis Gaya Kepemimpinan Kepala Madrasah Terhadap Penbentukan Karakter Guru MTsN 5 Aceh Utara - Muhammad Nur; Iskandar Iskandar (Al-Idaroh: Jurnal Studi Manajemen Pendidikan Islam, 2024)
The Madrasah Principal is an educational leader who has a very big role and is responsible for the educational process and also developing the character of teachers in the madrasah. Therefore, the author raised this research to analyze the leadership style of Madrasas at MTsN 5 North Aceh in forming teacher characters. This research is qualitative with a descriptive approach. Technique the researcher's data collection technique uses observation, interviews and documentation, while the data analysis technique is data reduction. The results of the research show that: The Madrasah Head's Leadership Style on the Formation of Teacher Character at MTsN 5 North Aceh is a democratic leadership style. The Impact of this Leadership Style on the Formation of Social Character of Teachers at MTsN 5 North Aceh shows a leadership attitude that is caring and oriented towards madrasa development, task assignments are carried out fairly, by ensuring that each individual accepts responsibility according to their abilities and roles. However, there are supporting and inhibiting factors in the formation of teacher character at MTsN 5 North Aceh, namely supporting factors, namely adequate teacher finances, adequate infrastructure and good personal relationships, which are created by teachers with fellow teachers, employees, parents, guardians, students and the surrounding community. Inhibiting factors come from several factors, can come from the teacher himself, or can come from factors outside the teacher such as students or from the teacher's work environment